A Prospective Study to Detect Immune Checkpoint Inhibitors Associated With Myocarditis Among Patients Treated for Lung Cancer - Faubry, Clara; Faure, Maxime; Toublanc, Anne-Claire; Veillon, Rémi; Lemaître, Anne-Iris; Vergnenègre, Charlotte; Cochet, Hubert; Khan, Sadia; Raherison, Chantal; Dos Santos, Pierre; Zysman, Maeva (Frontiers in Cardiovascular Medicine, 2022)
Background. Immune checkpoint inhibitors are widely used in lung cancer management. However, myocarditis which is a rare, yet potentially severe adverse related event associated with immune checkpoint inhibitors (ICIs), could be underreported. Objectives. The study aimed to prospectively evaluate the cumulative incidence rate of myocarditis, through systematic screening, among patients receiving ICIs for lung cancer. Methods. All patients receiving a first administration of ICIs for non-small and small lung cancer, between May and November 2020, in the pulmonary department of Bordeaux University Hospital, were included. ECG, troponin-I and natriuretic peptide dosages before ICIs' first administration and before each infusion were recorded. Echocardiography and magnetic resonance imaging were done additionally, in case of at least 3 times increase of troponin levels, ECG’s modifications and onset of cardiovascular symptoms. Secondly, coronoragraphy than endomyocardial biopsy if possible were assessed. The primary outcome was defined as ICIs related myocarditis onset, while secondary outcomes included other cardiovascular events, disease-free and overall survival. Results. During the period of interest, 99 patients received their 1st infusion of ICIs for lung cancer (mean age 64 ± 9 years; 52% men, 67% with adenocarcinoma). Three cases of myocarditis without major adverse cardiac event occurred (2 definite and 1 possible), and the mean duration between 1st ICIs’ administration and myocarditis onset was 144 ±3 days. Median disease-free survival and overall survival were 169 [102; 233] days and 209 [147; 249] days respectively. Conclusion. In our study, systematic screening of myocarditis associated with ICIs leads to a more frequent incidence and a later onset than previously reported. None of them were severe. Additional prospective evidence is needed before we could adopt routine cardiac screening in unselected patients starting ICIs, however these data shed a new light on the risk of myocarditis associated with ICIs administration.